Estimating daily global radiation from common meteorological variables in a humid subtropical environment - Teramoto, Erico Tadao [UNESP]; Silva e Cunha, Darllan Collins da [UNESP]; Santos, Cicero Manoel dos; Machado, Levi Pompermayer [UNESP]; Escobedo, Joao Franscisco [UNESP] (Univ Federal Mato Grosso, 2019)
Knowledge of solar potential is essential in the design and simulation of systems that convert solar radiation in electric power or available heat in fluids, as well as in agricultural studies focused on irrigation management and potential productivity assessment. Oftentimes, information about solar radiation are not available and, therefore, it becomes important the development of methods for obtain reliable data of solar radiation. The present study evaluated the performance of different methods of estimating global solar radiation (RG) in a Brazilian humid subtropical environment in order to determine which is more accurate. The meteorological databases used were registered by the automatic meteorological station belonging to the National Institute of Meteorology (INMET) and installed in Iguape, a municipality located in the Sao Paulo portion in the Ribeira Valley. Empirical models were calibrated and taken as reference in the performance evaluation of the Support Vector Machine (SVM) using different sets of input variables. Among the tested methods, the SVM using the set of input variables {R-0, T-max, T-min, e(smax), e(smin)} presented the best performance.
Keywords: empirical models; Ribeira Valley; SVM